PELAKSANAAN KOORDINASI INTERNAL KEPOLISIAN RESOR KAMPAR DENGAN POLRESTA PEKANBARU DALAM PENERBITAN SURAT KETERANGAN CATATAN KEPOLISIAN BERDASARKAN PERATURAN KEPALA KEPOLISIAN NEGARA REPUBLIK INDONESIA NOMOR 18 TAHUN 2014 TENTANG TATA CARA PENERBITAN SURAT KETERANGAN CATATAN KEPOLISIAN - H, PATAR ALEXANDER; ', Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Police Notes Certificate is officially given by the police to an individual citizen is concerned for the sake of fulfilling a request for such a purpose because of the prerequisite conditions based on the results of antecedents that person.That the Police Notes can take precautions against citizens ever committing a crime and facilitate the police in uncovering the incident or crime through the person's record notes. Then the execution of internal coordination within the agency and outside the region in agencies as well as with other agencies is needed in order to realize the internal security .In fact Execution in Kampar district police to Pekanbaru Police have not been able to run well purpose of this thesis is to find out; First, how the Implementation Coordination of Internal Police in Kampar to Pekanbaru Police Police Notes issuance. Secondly, what the Implementation Coordination constraints faced by Kampar district police in Publishing Pekanbaru Police Police Notes, Third, efforts to overcome the Implementation Coordination is not running and address of the Breach Publishing Police Notes. This research used kind of research Yuridis sosiologis that is seen by correlation between law and society. This research is done in society organization class II A pekanbaru, meanwhile population and sample is all of sides that relate with the problem that is researched. In this research, the source of data is used primer data, sekundar data and tertier data, technique for collecting the data in this research are interview, literature, and questioner From the research , there are three main things that can be concluded first , that the implementation of the Police Coordination Kampar and Pekanbaru Police are still not operating effectively . It started from the mechanism used and existing resources in Intelkam . Secondly, the obstacle in the implementation of the Coordination namely Infrastructures . Third , efforts to overcome the Implementation Coordination overcome are not going to make changes in the implementation mechanisms of publication , to evaluate the performance of the police , residents of the community to update the data every month , Improved Coordination of Internal and External .Keywords: Implementation - Internal Coordination - Publishing SKCK